Pengaruh suhu udara masuk terhadap massa air yang dihasilkan pada alat pemanen air sederhana - Mirmanto, M.; Nurpatria, N.; Hendra, J.K. (Dinamika Teknik Mesin, 2023)
An experimental investigation was performed to obtain the effect of air temperatures on the freshwater production of a simple water harvester. The amount of freshwater mass production depends on several variables, e.g. intake air temperature. For this reason, his study examined the relationship between the intake air temperature and the mass of freshwater production. The research was conducted experimentally with R134a refrigerant as the working fluid and the intake air temperatures tested were 30°C, 35°C, and 40°C. The results show that the highest freshwater mass production was 0.340 kg at the intake air temperature of 30°C. Meanwhile, the highest coefficient of performance was 9.12 at the same intake air temperature and the highest total heat transfer rate was 184.16 W at the intake air temperature of 40°C. The effect of the intake air temperature on the mass of water, coefficient of performance and the total heat transfer rate was not clear.